2007
DOI: 10.1007/s11920-007-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Advances in crisis management of the suicidal patient: Perspectives from patients

Abstract: This paper discusses crisis intervention with the suicidal client from the perspective of two clients who discuss both the strengths and challenges they have encountered while in crisis. The paper then discusses a model for understanding a suicidal crisis and a template for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…These authors further purport that DBT is the only psychosocial treatment shown in multiple randomized clinical trials to be effective for BPD and suggest that DBT may be uniquely effective in treating suicidal individuals. Interestingly, very similar findings can be located in the encouraging and robust work emanating from St. Michael's Hospital and/or University of Toronto (see Bergmans & Links 2002; Bergmans et al . 2007).…”
Section: National Suicide Prevention Strategy Documents: Commonalitiementioning
confidence: 54%
See 1 more Smart Citation
“…These authors further purport that DBT is the only psychosocial treatment shown in multiple randomized clinical trials to be effective for BPD and suggest that DBT may be uniquely effective in treating suicidal individuals. Interestingly, very similar findings can be located in the encouraging and robust work emanating from St. Michael's Hospital and/or University of Toronto (see Bergmans & Links 2002; Bergmans et al . 2007).…”
Section: National Suicide Prevention Strategy Documents: Commonalitiementioning
confidence: 54%
“…These authors further purport that DBT is the only psychosocial treatment shown in multiple randomized clinical trials to be effective for BPD and suggest that DBT may be uniquely effective in treating suicidal individuals. Interestingly, very similar findings can be located in the encouraging and robust work emanating from St. Michael's Hospital and/or University of Toronto (see Bergmans & Links 2002;Bergmans et al 2007). Focusing on a population of people diagnosed with a BPD who had made recurrent suicide attempts, these researchers enlisted 147 individuals in a 20 week group intervention aimed at de-escalating the individuals' emotional (psychache) crisis and providing the population with an enhanced ability to identify and/or express their distressing emotions (given that these individuals all had high alexithymia scores).…”
Section: Development and Promotion Of Effective Clinical And Professimentioning
confidence: 55%
“…Training in DBT (see Linehan 2007) and the approach that focuses on de-escalating an individuals' emotional (psychache) crisis and providing the person with an enhanced ability to identify and/or express their distressing emotions (Bergmans & Links 2002;Bergmans et al 2007) have been covered previously. Therefore, the authors will concentrate on the approach that focuses on engagement, inspiring hope, and reconnecting the person with humanity.…”
Section: Improving Observations and Tightening Up Policiesmentioning
confidence: 99%
“…Training in DBT (see Linehan 2007) and the approach that focuses on de‐escalating an individuals' emotional (psychache) crisis and providing the person with an enhanced ability to identify and/or express their distressing emotions (Bergmans & Links 2002; Bergmans et al . 2007) have been covered previously.…”
Section: Introductionmentioning
confidence: 99%
“…Discourses underpinning the desire for predictability and control also give rise to contradictory pulls within the professional, such as competing beliefs about the person"s value as an individual (Joyce et al, 2007) and deservedness of care (Bergmans et al, 2007), which can serve to reinforce young men"s sense of difference and powerlessness.…”
Section: Enacting a New Worthy Identitymentioning
confidence: 99%